Demokracja dyskursywna w myśleniu politycznym - Zyborowicz, Stanisław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The paper concerns one of the concepts of democracy. Each democracy assumes that the people who live together in society need certain procedures/institutions to make binding decisions that take into consideration everybody’s interests. The notion of a deliberative democracy is used to describe a system of political decisions based on the decision-making process perceived as a combination of consensus and representative democracy. Discursive democracy is a theoretical model of a political system propagated by Jurgen Habermas and Jon Elster, and also by Joshua Cohen, Amy Gutmann and Dennis Thompson. The concept was used for the first time by Joseph M. Bessette in his work Deliberative Democracy: The Majority Principle in Republican Government in 1980, and later on in The Mild Voice of Reason in 1994. Public debate is a key aspect of the discursive concept which emphasizes the manner in which all arguments are presented in open discussion. Discursive democracy assumes a larger participation of citizens in the legislative process by means of institutionalized debates organized to complement the process of informal opinion shaping. Deliberative democracy will win an increasing number of proponents. This certainly is not only a matter of will but also of realistic opportunities to participate in the process of building a deliberative democracy.